Dynamics of the Serine Chemoreceptor in the Escherichia coli Inner Membrane: A High-Speed Single-Molecule Tracking Study - Oh, Dongmyung (The Biophysical Society, 2014)
We investigated the mobility of the polar localized serine chemoreceptor, Tsr, labeled by the fluorescent protein Venus in the inner membrane of live Escherichia coli cells at observation rates up to 1000 Hz. A fraction (7%) of all Tsr molecules shows free diffusion over the entire cell surface with an average diffusion coefficient of 0.40 ± 0.01 μm(2) s(−1). The remaining molecules were found to be ultimately confined in compartments of size 290 ± 15 nm and showed restricted diffusion at an inner barrier found at 170 ± 10 nm. At the shortest length-scales (<170 nm), all Tsr molecules diffuse equally. Disruption of the cytoskeleton and rounding of the cells resulted in an increase in the mobile fraction of Tsr molecules and a fragmenting of the previously polar cluster of Tsr consistent with a curvature-based mechanism of Tsr cluster maintenance.